2022
DOI: 10.3390/ijerph192013459
|View full text |Cite
|
Sign up to set email alerts
|

Does Early Childhood Caries Increase Caries Development among School Children and Adolescents? A Systematic Review and Meta-Analysis

Abstract: The aim of this paper is to systematically review the literature to determine whether early childhood caries (ECC) is significantly associated with caries development in permanent teeth among school children and adolescents, and to identify the association of other risk factors over 24 months. A systematic literature search was performed in four electronic databases and via a manual search from inception to 28 July 2022. Independent study selection and screening, data extraction, evaluation of risk of bias usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 42 publications
(123 reference statements)
0
8
0
2
Order By: Relevance
“…A recent systematic review primarily identified low level of maternal education as a risk factor for future caries development [39]. A greater caries experience was found in child participants whose "less educated" mothers introduced them to sugar before 12 months old compared to those where sugar was introduced after 24 months of age.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review primarily identified low level of maternal education as a risk factor for future caries development [39]. A greater caries experience was found in child participants whose "less educated" mothers introduced them to sugar before 12 months old compared to those where sugar was introduced after 24 months of age.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reflect how all social classes have a similar potential to develop caries, and although socioeconomic class has been considered a determinant factor, it is families with a poorer socioeconomic position that have a higher susceptibility to more severe stages of disease [ 17 ]. However, some authors have found weak evidence of the association of socioeconomic behavior factors and oral health [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Пропаганда знань про догляд за порожниною рота та формування відповідних звичок і безпечного харчування є необхідною із раннього віку для формування відповідних звичок у дорослому віці. Для подолання негативного впливу низького рівня стоматологічного здоров'я у дитячого населення наявна актуальна потреба в дослідженні та розумінні детермінант, які призводять до нерівності такого здоров'я [6][7][8][9][10].…”
Section: двнз «ужгородський національний університет» ужгород українаunclassified